Forming a scientific worldview and thinking. The worldview is a system of dialectical views - Atajanova Gulbaxar Yusupovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article contains new teaching methods to improve the assimilation of high volume of information, improving student engagement to the classes, pointed details that teacher should pay attention, moreover described the aspects of intensive communication